The Role of Motor Experience in Understanding Action Function: The Case of the Precision Grasp - Loucks, Jeff (2012)
Recent evidence suggests adults and infants selectively attend to features of action, such as how a hand contacts an object. The current research investigated whether this bias stems from infants’ processing of the functional consequences of grasps: understanding that different grasps afford different future actions. A habituation paradigm assessed 10-month-old infants’ (N = 62) understanding of the functional consequences of precision and whole-hand grasps in others’ actions, and infants’ own precision grasping abilities were also assessed. The results indicate infants understood the functional consequences of another’s grasp only if they could perform precision grasps themselves. These results highlight a previously unknown aspect of early action understanding, and deepen our understanding of the relation between motor experience and cognition.